Study on the pattern of radiological changes in osteoarthritis of knee joint - Ahmed, SM; Rahman, MA; Islam, MT; Khasru, MR; Islam, MA (Bangladesh Medical Journal, 2014)
Knee osteoarthritis (OA) is one of the frequent and functionally impairing disorders of the musculoskeletal system and characterized by an imbalance between the synthesis and degradation of the articular cartilage. The present study was conducted on the pattern of radiological changes in OA of knee joint patients attending in the department of Physical Medicine & Rehabilitation of Bangabandhu Sheikh Mujib Medical University. Structural changes of articular cartilage were assessed by the sequence of changes in the knee joint manifested as sclerosis, osteophytes formation, and joint space narrowing and joint space erosion by a radiographic examination. Osteophytes were more common in medial condyle in 46-61 age group (73.68%) and male patients of some age group showed higher rate of development of osteophytes in intercondylar area. Narrowing of joint space were more in medial tibiofemoral compartment (59.82%) in the 46-61 age group (70.98%), where as erosion was found higher in medial tibiofemoral compartment (70%) and more in male patients (36%). The findings of this study as revealed by the standard radiographic imaging of formation of osteophytes, joint space narrowing and joint space erosion lead to the recommendation that the problem is increasing with age. However, more studies are required for the purpose specifying medical treatment using appropriate appliances under close supervision of a physical medicine specialist. DOI: http://dx.doi.org/10.3329/bmj.v42i1.18972 Bangladesh Med J. 2013 Jan; 42 (1): 14-17